2022
DOI: 10.1021/acssuschemeng.1c07662
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Protic Ionic Liquids as Sustainable Solvents for Wool Keratin/Cellulose Simultaneous Dissolution: Solution Properties and Composited Membrane Preparation

Abstract: In this study, levulinic acid-derived protic ionic liquids (PILs) were identified to be good solvents for wool keratin fiber dissolution and the simultaneous dissolution of wool keratin and cellulose, implying a green dissolution processing platform for regenerated materials preparation derived from both cellulose and keratin. The satisfactory solubility was believed to correlate to the potential keto–enol tautomerism of the ketone group in the levulinate anion, which has particular hydrogen bonding forming ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 82 publications
2
25
0
Order By: Relevance
“…There was a significant vibrational peak associated with OH stretching in the 3491–3442 cm −1 range and absorption bands associated with CH 2 and CO stretching vibrations at around 2975 and 1062 cm −1 , respectively 29,30 . If the intermolecular hydrogen bonding is larger than the strength of the intramolecular hydrogen bonding, and vice versa, the associated hydroxyl band will shift toward a lower wavenumber 31,32 . With increasing VBz ratios, it was revealed that the peak of the OH stretching vibration absorption shifted from 3491 cm −1 to a lower wavenumber of 3442 cm −1 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…There was a significant vibrational peak associated with OH stretching in the 3491–3442 cm −1 range and absorption bands associated with CH 2 and CO stretching vibrations at around 2975 and 1062 cm −1 , respectively 29,30 . If the intermolecular hydrogen bonding is larger than the strength of the intramolecular hydrogen bonding, and vice versa, the associated hydroxyl band will shift toward a lower wavenumber 31,32 . With increasing VBz ratios, it was revealed that the peak of the OH stretching vibration absorption shifted from 3491 cm −1 to a lower wavenumber of 3442 cm −1 .…”
Section: Resultsmentioning
confidence: 97%
“…29,30 If the intermolecular hydrogen bonding is larger than the strength of the intramolecular hydrogen bonding, and vice versa, the associated hydroxyl band will shift toward a lower wavenumber. 31,32 With increasing VBz ratios, it was revealed that the peak of the OH stretching vibration absorption shifted from 3491 cm À1 to a lower wavenumber of 3442 cm À1 . This is mainly due to the special structure of the benzene ring on the side group of VBz has a great steric hindrance effect, 27 during the polymerization, the arrangement structure of the side groups of the original prepolymer was changed, and more hydrogen bonds were formed between the OH groups after alcoholysis.…”
Section: Ftir Characterization Of Pva Polymersmentioning
confidence: 99%
“…The disadvantages of this method are that it is time consuming and can easily introduce impurities. In order to improve the properties of keratin-based biofilms, many natural polymers as modifiers, such as sodium alginate, gelatine, chitosan, cellulose, pullulan, and silk fibroin may be introduced into the casting solution [ 102 , 103 , 104 , 105 , 106 , 107 , 108 ].…”
Section: Preparation Methods Of Keratin-based Biofilmsmentioning
confidence: 99%
“…But using cellulous entirely "naturally" limits its usefulness (He et al 2022), it is worth noting that the high value utilization of cellulose requires dissolution and regeneration processes (Acharya et al 2021). Usually, the solution processing route includes structural dissociation (Deng et al 2022) and regeneration (Sirviö 2019), and the regenerated structures decide the properties and applications of the cellulosic materials (Qiu et al 2022).…”
Section: Introductionmentioning
confidence: 99%